Electrospray interfacial polymerization for a loose NF membrane: super-selective dye separation in saline dye wastewater treatment. Issue 11 (29th September 2021) - Kang, Yesol; Jang, Jaewon; Lee, Yunho; Kim, In S.
Abstract : A loose nanofiltration membrane fabricated by electrospray interfacial polymerization which contained a tiny amount of sulfonated graphene oxide nanoparticles showed excellent water permeance and salt/dye separation. Abstract : A sulfonated graphene oxide (SGO) composite loose nanofiltration membrane (LNM) with high water permeance was fabricated by the electrospray interfacial polymerization (EIP) method to treat saline dye wastewater. The SGO incorporated EIP membrane showed enhanced characteristics and performances even with a small amount of nanoparticles (0.04 g per membrane area (m 2 )). The SGO was uniformly dispersed on the membrane surface by means of an electrospray that ejects nano-sized droplets. The fabricated LNM with 2000 mg L −1 SGO has the highest water permeance of 16.7 ± 2.2 LMH bar −1, which increased by 53% compared with that of the pristine membrane (11.0 ± 0.8 LMH bar −1 ), and showed superior specific selectivity with high rejection for Evans blue (Mw = 960.8, 99.6%) and Congo red (Mw = 696.7, 99.8%) with high NaCl permeation (92.3%). The surface roughness of the membrane decreased and the hydrophilicity and negative charge were enhanced with increasing concentration of SGO. These properties improved the antifouling property of the membrane as the flux recovery rate (FRR) of the SGO embedded membrane remained at 97.9% after the reusability test. This work provides a facile approach to prepare highly efficient loose nanocomposite nanofiltration membranes for dye wastewater treatment.